The Role of Hunayn ibn Ishaq in the Transformation of Greek Knowledge into the Islamic World during the Abbasid Era - Ramadani, Achmad Arfiansyah; Ningrum, Anggun Dian (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to explore the role of Hunayn ibn Ishaq in transmitting Greek knowledge to the Islamic world, particularly during the golden age of the Abbasid Dynasty. The main focus of this work is to scientifically uncover Hunayn's intellectual contributions through his translations of important works by Greek thinkers such as Galen and Hippocrates, positioning him as a bridge between the Greek intellectual legacy and the Islamic scientific tradition. In the context of the development of Islamic knowledge, Hunayn's role was crucial because he did not merely translate texts literally, but also interpreted and adapted classical scientific concepts.This article employs a library research method with a descriptive-analytical approach. The findings indicate that Hunayn functioned not only as a translator but also as a scholar who filtered, reorganized, and even corrected Greek texts to make them more accessible and applicable for development by subsequent generations of Muslim scientists. His works became a foundational pillar for the growth of scientific tradition in the Islamic world and had a significant influence that extended into the European Renaissance.